GIS based mapping and analysis of landslide hazard’s impact on tourism: a case study of Balakot valley, Pakistan - Hussain, Alamgeer; Riaz Khan, Mobushir; Abbas Malik, Naeem; Amin, Muhammad; Hussain Shah, Mazhar; Naveed Tahir, Muhammad (International Journal of Advanced Geosciences, 2017)
The Landslide occurs in mountainous area due to failure of slope through intensive rain and earthquake. Region wise Himalayan is one of prone area of world in context of slope failure hazard; i.e. Landslide, especially Balakot valley is well known for damage of public infrastructure, roads and badly affected the tourism sector. The objective of this study is to develop landslide hazard map and database inventory of balakot tehsil and identify the Tourist resorts landslide hazard condition and hazard prone road site and developed guidelines for tourist about hazardous site and their intensity of landside, which could be useful for tourism sector and sustainable development in balakot valley. In this study we used weighted overlay analysis in arc GIS environment on primary and secondary data raster layers, like slope map, Slope Aspect map, precipitation and seismic raster maps were used to develop landslide hazard zonation map of balakot tehsil. Slope and Aspect map were developed using 30 meter aster digital elevation model. Precipitation map were developed through Inverse Distance weighted (IDW) interpolation method on annual precipitation data acquired from Pakistan meteorological department. Seismic map were acquired from Geological Survey of Pakistan (GSP). Landslide zonation map has three hazards class high, Medium and low. The landslide exposure of high hazard class 499 sq.km while, Medium class 1016 sq.km and low hazard class having 749 sq. km exposure in balakot tehsil respectively. Landslide hazard zonation mapping using GIS and RS is the best way to assess the risk of landslide hazard in mountainous areas. The study recommended that ground penetrating radar (GPR) and soil testing based research well help to understand in-depth of landslide hazard condition in balakot valley.